Laryngeal distribution of adult‐onset recurrent respiratory papillomatosis: A longitudinal study. (6th May 2019) - Hu, Lizbeth; Benedict, Peter A.; Garber, David; Wang, Binhuan; Amin, Milan R.; Branski, Ryan C.
Abstract : Objectives/Hypothesis: To describe recurrence patterns in patients with recurrent respiratory papillomatosis (RRP) following surgical intervention. Study Design: Single‐center, retrospective, longitudinal case series. Methods: Initial and follow‐up laryngoscopic examinations of seven previously untreated adult‐onset RRP patients were reviewed. Patients were followed longitudinally for periods ranging from 3 months to 7 years. Lesion locations were recorded using a twenty‐one region laryngeal schematic, and maps were generated to illustrate the distribution of disease before and after cold‐knife or potassium‐titanyl‐phosphate laser intervention. Univariate and multivariate analyses were employed to examine variables affecting recurrence patterns. Results: Across all patients, a statistically significant correlation between initial distribution and primary recurrence was observed. Seventy‐five percent of new lesions were adjacent to regions with preexisting disease; 83% of new glottic lesions were adjacent to preexisting glottic lesions, and 66% of supraglottic lesions were adjacent to preexisting supraglottic regions. No statistically significant differences in recurrence rate were observed across sites. Conclusions: In previously untreated patients with adult‐onset recurrent respiratory papillomatosis, lesions tended to recur either in the same regions or regions adjacent to those affected at the time of initial surgery. Level of Evidence: 4 Laryngoscope, 129:1993–1997, 2019